Evaluation of Risk Factors Affecting Progression in Primary Open-Angle Glaucoma and Exfoliation Glaucoma in a Turkish Population - Ağın, Abdullah; İrkeç, Murat and Kocabeyoğlu, Sibel and Karakaya, Jale (Acta Medica, 2022)
Objective: To evaluate the effects of risk factors on progression in primary open-angle glaucoma (POAG) and exfoliation glaucoma (XFG). Materials and methods: The study included 139 patients with POAG and XFG followed up at Hacettepe University Faculty of Medicine, Department of Ophthalmology, Glaucoma Unit. A number of factors were evaluated through a cross-sectional design for all the patients, including age, sex, hypertension, diabetes, thyroid disease, cardiovascular disease, migraine, alcohol, smoking, family history, affected side, lens status, central corneal thickness (CCT), number of medications, body mass index (BMI), cup-to-disc (C/D) ratio, intraocular pressure (IOP), computerized automated visual field mean deviation (MD), and prior surgery. Results: The patients were divided into two groups, POAG and XFG, and further divided into the following two subgroups: progressive and non-progressive. Of the patients, 75 (53.9%) had POAG, and 64 (46.1%) had XFG. In the patients followed up, annual MD change was 0.96 ± 1.5 dB/year, baseline MD was −5.06 ± 5.61 dB, and IOP was 15.94 ± 1.93 mmHg. Potential risk factors for progression in the whole group were evaluated, but no significant difference was found between the groups with and without progression for all factors. Subgroup analysis revealed that in the POAG group, BMI was significantly higher in the non-progressive disease subgroup (p=0.01); furthermore, in the XFG group, IOP was significantly higher in the progressive disease subgroup (p=0.02). According to multiple logistic regression analysis, a 1-unit decrease in BMI in the POAG group increased the risk by 1.3 times (p=0.01), and smoking in the XFG group resulted in a 6-fold reduction in the risk of progression (p=0.04). Conclusion: Although mean IOP was higher in XFG group, the present study found BMI in POAG and smoking in XFG as independent factors that reduced progression in our series.